Audit committees and fraudulent financial reporting: a descriptive analysis - Puat Nelson, Sherliza (2011)

(untitled)
The study examines the background of the audit committee from the aspect of professional affiliations, postgraduate qualifications and senior managerial experiences, in association with fraudulent financial reporting.